The TIR/BB‐loop mimetic AS‐1 prevents non‐alcoholic steatohepatitis and hepatic insulin resistance by inhibiting NLRP3‐ASC inflammasome activation. (26th April 2017) - Wang, Xiaolu; Gao, Yun; Song, Juan; Tang, Chao; Wang, Man; Que, Linli; Liu, Li; Zhu, Guoqing; Chen, Qi; Yao, Yong; Xu, Yong; Li, Jiantao; et al.
Abstract : Background and Purpose: Non‐alcoholic steatohepatitis (NASH) is characterized by excessive intracellular lipid accumulation, inflammation and hepatic insulin resistance. As the incidence of NASH is increasing worldwide, there is an urgent need to find novel interventional approaches. The pro‐inflammatory cytokine IL‐1β, generated and released from Kupffer cells, is considered to initiate the development of NASH. AS‐1, a synthetic low‐molecule mimetic of myeloid differentiation primary response gene 88 (MyD88), disrupts the interaction between the IL‐1 receptor and MyD88. Here, we investigated whether AS‐1 could attenuate the pathogenesis of NASH with an emphasis on hepatic insulin resistance. Experimental Approach: Eight‐week‐old db/db mice were fed a control diet or a methionine‐ and choline‐deficient (MCD) diet. AS‐1 (50 mg·kg −1 ) or vehicle was administered i.p. Key Results: AS‐1 administration significantly ameliorated NASH as evidenced by alanine aminotransferase levels and CD68 levels in livers of MCD‐fed mice. AS‐1 inhibited the MCD diet‐induced activation of caspase 1 and the NLRP3‐ASC inflammasome, and also reduced the enhanced levels of ROS, malondialdehyde, 3‐nitrotyrosine, NADPH oxidase complex and CYP reductase‐associated cytochrome p450 2E1 (CYP2E1) expression in the liver. In addition, AS‐1 decreased ROS, inflammasome activation and IL‐1β production in free fatty acid‐LPS‐treated Kupffer cells. Finally, pretreatment with AS‐1 significantly ameliorated gluconeogenesis and insulin desensitization induced by IL‐1β, probably by blocking the interaction between MyD88 and the IL‐1 receptor. Conclusions and Implications: Our results indicate that AS‐1 can ameliorate NASH and hepatic insulin resistance and could be considered as a potential strategy for the prevention and treatment of NASH.